Legal Analysis of Violence by the Gank Gaza Group in Bali: A Review of Cases and Law Enforcement - Upadana, I Kadek Satria; Sujana, I Nyoman (International Journal of Education, Culture, and Society, 2025)
This research examines acts of violence by the "Gank Gaza" group in Bali, highlighting legal dynamics and challenges in effective law enforcement. The study analyzes a series of cases involving the group's violence, identifying the patterns and motivations behind their actions. Through a juridical-sociological approach, this research evaluates the response of law enforcement officials, highlighting structural and operational weaknesses that hinder optimal handling. The results of the analysis show the need to increase law enforcement capacity through special training, strengthening intelligence, and collaboration between institutions. The study also emphasizes the importance of preventive approaches, including youth empowerment programs and community awareness campaigns, to address the root causes of gang violence. Thus, this research provides strategic recommendations to strengthen the legal system and create a safer environment in Bali.